Enhancing Performance in Co-Curricular Activities Through Structured Approach in Minor Projects - Hublikar, Shivaraj; Mudengudi, Uma; Kumar, Priyatam; Shettar, Rajashekar B.; Kakhandki, Arun; Patil, Soumya S. (Journal of Engineering Education Transformations, 2016)
This paper discusses the process of enhancing the student’s performance through minor project. Minor projects are typically carried out in third year of four year engineering graduation. In this paper the rubrics based evaluation is defined to enhance the minor project experiences. Minor projects are one of the platform to showcase integrated learning experience. The defined rubrics are based on engineering design process. The experiment is done on 2012-2016 batch of 6th semester students. Performances of the students are show-cased through co-curricular activities and by participating in various competitions held across the country. With this practice achievement in co-curricular activity participation is increased from15% to 65%for previous year batch.